Analysis Characteristics and Performance Intersections Signal Rawa Panjang Related to Odd-Even Policy on West Bekasi Toll Door - Dermawan, Widodo Budi; Chalimin, Ahmad (NAROTAMA UNIVERSITY, Indonesia, 2020)
The application of Odd-Even policies on the Bekasi West Toll door to unravel the volume of traffic on the Jakarta-Cikampek Toll Road, with the hope that motorists can use public transportation provided by the government so that they can also decipher the volume of traffic flow within the city. Bekasi itself, especially in the main intersections in the city. The method used for collecting data is primary data and secondary data. Primary data is data taken through direct observation in the real field. Primary data consists of vehicle volume data and actual conditions of intersections such as side barriers. Secondary data is data on road size, road conditions and completeness, and population. Furthermore, for this study, the calculation method used the reference available in the 1997 Indonesian Road Capacity Manual (MKJI). From the results of the analysis, the performance of long swamp signal intersections at maximum currents has Level Of Service (LOS) or level F service intersection (very bad) as a result of high delay values usually indicate long cycle times and high vehicle ratios. Solutions that can be obtained are implementing regulations that have been adjusted to the conditions of the intersection, removing side barriers that often occur in each approach, widening the road in one approach and rearranging the cycle time at the intersection